Diagnosis, Prognosis and Treatment of Canine Cutaneous and Subcutaneous Mast Cell Tumors - Andrigo Barboza de Nardi; Rodrigo dos Santos Horta; Carlos Eduardo Fonseca-Alves; Felipe Noleto de Paiva; Laís Calazans Menescal Linhares; Bruna Fernanda Firmo; Felipe Augusto Ruiz Sueiro; Krishna Duro de Oliveira; Silvia Vanessa Lourenço; Ricardo De Francisco Strefezzi; Carlos Henrique Maciel Brunner; Marcelo Monte Mor Rangel; et al. (Cells, 2022)
Mast cell tumors (MCTs) are hematopoietic neoplasms composed of mast cells. It is highly common in dogs and is extremely important in the veterinary oncology field. It represents the third most common tumor subtype, and is the most common malignant skin tumor in dogs, corresponding to 11% of skin cancer cases. The objective of this critical review was to present the report of the 2nd Consensus meeting on the Diagnosis, Prognosis, and Treatment of Canine Cutaneous and Subcutaneous Mast Cell Tumors, which was organized by the Brazilian Association of Veterinary Oncology (ABROVET) in August 2021. The most recent information on cutaneous and subcutaneous mast cell tumors in dogs is presented and discussed.